Numerical modelling of landfill lining system–waste interaction: implications of parameter variability. Issue 5 (October 2012) - Sia, A.H.I.; Dixon, N.
Abstract : ABSTRACT: Numerical modelling techniques can be used to examine the serviceability limit states of landfill side-slope lining systems in response to waste placement. A study has been conducted in which the variability of significant model input parameters have been investigated within a probabilistic framework using Monte Carlo simulation. Key model parameters are treated as random variables, and the statistical information required to describe their distributions has been derived from a laboratory repeatability testing programme, a literature survey and an expert consultation process. Model outputs include relative shear displacements between lining components, and tensile strains in the geosynthetic layers that occur in response to staged placement of waste against the side slope. It was found that analyses including input parameter variability were able to identify mechanisms influencing liner performance and their probability of occurrence. These mechanisms include large (i.e. ≫100 mm) relative displacements at interfaces that can generate post-peak strengths, and mobilised tensile strains in the geomembrane and geotextile layers. Additionally, it was found that relative displacements at the controlling (i.e. weakest) liner interface are greater for landfills with a steep side slope, for stiffer waste and thicker waste lifts, while tensile strains in the geosynthetic elements are greater for steep side slopes, more compressible waste and thinner waste lifts. Outputs from probabilistic analyses such as that used in this study can guide engineers regarding geometries and materials that could produce waste-settlement-generated serviceability limit state failures, and hence can be used to support more reliable designs.